Perception of stakeholders on abandoned housing projects: case for Malaysia - Abdul Razak, Dzuljastri; Mohd Ariffin, Noraini; Mohamed Noorden, Mohamed Imtiyaz (2016)
Home is a basic necessity for everyone. However, one of the major issues affecting the construction industry in Malaysia today is that of abandoned housing projects (AHPs). This issue has caused sufferings to the individuals and society. Several reasons have been cited for the AHPs which include the debt financing structure, lack of justice and fairness, and weak regulatory system. The issues of the Islamic banking debt based home financing products have remained prominent. There are also other issues such as role of the authority in addressing the situations. This study used mixed method of surveys and interviews in determining the perceptions of stakeholders regarding AHPs. The outcome of study highlights various prospects of mitigating the problem of abandoned housing projects.